Effects of Phloroglucinol on In Vitro Methanogenesis, Rumen Fermentation, and Microbial Population Density - Sarwono, K. A.; Kondo, M.; Ban-Tokuda, T.; Jayanegara, A.; Matsui, H. (Tropical Animal Science Journal, 2019)
This study investigated the effect of phloroglucinol (1,3,5-trihydroxybenzene) supplementation alone on methane production, rumen fermentation profiles, and microbial population structure of mixed in vitro cultures. Treatments included a control group containing a substrate with no supplement, and substrates supplemented with 2, 4, 6, 8, or 10 mmol/L of phloroglucinol. The results revealed that phloroglucinol was able to decrease methane production in a dose-dependent manner. The highest decrease was observed with 8 and 10 mmol/L supplementations. The relative quantity of methanogen was not affected by phloroglucinol, whereas genus Coprococcus was increased with increasing concentrations of phloroglucinol (p<0.05). Total gas production, dry matter digestibility (DMD), and NH3-N were significantly lowered by phloroglucinol (p<0.001). Total short-chain fatty acid (SCFA) concentration was not affected by phloroglucinol. Acetate proportion increased with the addition of phloroglucinol at the expense of propionate (p<0.001). This might indicate the redirection of [H] from methane to acetate, and might be related to methane inhibition.. Our study concluded that supplementation of phloroglucinol alone could decrease methane production by inhibiting nutrient digestibility in the rumen and by possible redirection of rumen fermentation to acetate production. Genus Coprococcus could be an important actor for phloroglucinol metabolism in the rumen.